Isolation, Identification, Serotyping And Antibiotic Resistance Pattern Of Salmonella Isolated From Fecal Samples Of Kites - Pawade , M.M.; Budhe, S.D. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Salmonella is an important zoonotic pathogen of economic importance. The present study was carried out to investigate serotypes and drug resistance pattern of Salmonella isolated from fecal samples of kites. Out of 40 fecal samples screened, only 3 samples were found positive for Salmonella. All the 3 isolates were studied for their antibiotic sensitivity pattern employing disc diffusion technique using commercial antibiotic discs. In vitro Antibiotic sensitivity pattern of these Salmonella isolates against 11 antibiotics revealed highest sensitivity towards chloramphenicol, gentamycin and ciprofloxacin followed by neomycin, cefotaxime, ofloxacin norfloxacin and amoxyclav. The organisms were found resistant towards streptomycin, tetracycline, and ampicillin. The present findings indicate that the kites may harbor organisms like Salmonella which may pose human health hazards.